Use of pleural fluid ceruloplasmin in the differentiation of exudative and transudative pleural effusion - Shanthaveeranna, Girish K. (Lung India, 2015)
BACKGROUND: Differentiating into transudate or exudate is the first step in the evaluation of effusions. Light's criteria is the standard but a significant number of transudates may not be differentiated based on these criteria. Acute phase proteins (APP) are present in plasma, which increase or decrease by about 25% during an acute inflammatory response. Ceruloplasmin (CP) is a positive APP. Hence, this study was done to know the diagnostic value of pleural fluid (pf) CP and pf to serum ceruloplasmin ratio (CPr) to differentiate the pleural effusion (PE) into exudate and transudate as compared to Light's criteria. MATERIALS AND METHODS: Setting: Medical wards of St John's Medical College Hospital, Bangalore. DESIGN: Cross-sectional descriptive study. Patients with PE were divided into exudate and transudate by definitive diagnosis. pfCP, CPr and Light's criteria were compared with definitive diagnosis for the differentiation of pf into exudate and transudate. RESULTS: The mean value of the pfCP and CPr was found to be significantly different between exudates and transudates. Sensitivity and specificity of pfCP at ≥ 13.34 mg/dl is 89.7% and 83.3%, CPr at ≥ 0.37 is 91.4% and 83.3%, Light's criteria 94.82% and 83.3%, respectively. Light's criteria, pfCP and CPr have similar PPV (98%) with Light's criteria having higher NPV (62.5%) than pfCP (45%) and CPr (50%), respectively. CPr has higher NPV than pfCP. CONCLUSIONS: pfCP and CPr can differentiate pf into exudate and transudate with comparable PPV to Light's criteria.